Multimodal argumentation in news magazine covers: A case study of front covers putting Greece on the spot of the European economic crisis. (March 2015) - Tseronis, Assimakis
Abstract: In this paper, front covers of news magazines are studied as a distinct multimodal genre that invites readers to buy the magazine not only by attracting their attention but also by assuming a position with respect to the particular cover story. In order to account for the argument that a front cover may convey in support of that position, an argumentative reconstruction is required that also needs to take seriously into account the way in which the verbal and the visual modes interact to create meaning. The study proposes a multimodal argumentation perspective on the systematic reconstruction of the arguments that front covers of news magazines put forward. As a case in point, six covers by two German weekly news magazines are analysed, featuring the role of Greece in the eurozone crisis in the period 2010–2012. Highlights: Studies news magazine covers as a multimodal genre that advances a complex argument. Focuses on the argumentative relevance of the verbal–visual interaction. Expands the object of argumentation studies into multimodal communicative genres. Applies multimodal argumentative analysis on the context of the eurozone crisis.